Effects of venous needle turbulence during ex vivo hemodialysis on endothelial morphology and nitric oxide formation - Huynh, Thanh N.; Chacko, Balu K.; Anayiotos, Andreas (My University, 2007)
Arteriovenous grafts used for hemodialysis frequently develop intimal hyperplasia (IH), which ultimately leads to graft failure. Although the turbulent jet from the dialysis needle may contribute to vessel wall injury, its role in the pathogenesis of IH is relatively unexplored. In the current study, using bovine aortic endothelial cells (BAEC) cultured on the inner surface of a compliant tube, we evaluated the effects of simulated hemodialysis conditions on morphology and nitric oxide (NO) production. The flows via the graft and needle were 500 ml/min (Reynolds number = 819) and 100 ml/min (Reynolds number = 954), respectively. In the presence of the needle jet for 6 h, 19.3% (±1.53%) of BAEC were sheared off, whereas no loss of BAEC was observed in the presence of graft flow alone (P < 0.05). In the presence of graft flow alone, assessment of cell orientation by the Saltykov method revealed that BAEC were oriented along the flow direction. This alignment, however, was lost in the presence of needle flow. Finally, NO production was also significantly decreased in the presence of the needle flow compared to the presence of graft flow alone (16 ± 3.1 vs 34.7 ± 1.9 nmol / 1 0 6 cells / h, P < 0.05). NO is a key player in vascular homeostasis mechanisms modulating vasomotor tone, inhibiting inflammation and smooth muscle cell proliferation. Thus, the loss of NO signaling and the loss of endothelial integrity caused by needle jet turbulence may contribute to the cascade of events leading to IH formation during hemodialysis.
Keywords: ascular endothelial cells; Hemodialysis; Nitric oxide